Peripheral cemento-ossifying fibroma in child. A follow-up of 4 years. Report of a case - Delbem, Alberto Carlos Botazzo [UNESP]; Cunha, Robson Frederico; Silva, Janaína Zavitoski; Soubhia, Ana Maria Pires (European Journal Of Dentistry, 2008)
Peripheral cement-ossifying fibroma is a relatively common gingival growth of a reactive rather than neoplastic nature, whose pathogenesis is uncertain. It predominantly affects adolescents and young adults, with peak prevalence between 10 and 19 years. We report here the clinical case of a 5-year-old girl with disease duration of 3 years, who was followed up for 4 years, showing a gingival health and normal radiopacity of bone.
Keywords: Oral tumors; Peripheral cemento-ossifying fibroma; Pyogenic granuloma